2018
DOI: 10.15326/jcopdf.5.4.2018.0157
|View full text |Cite
|
Sign up to set email alerts
|

National and State Estimates of COPD Morbidity and Mortality — United States, 2014-2015

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 3 publications
3
76
1
1
Order By: Relevance
“…In the USA, 12 million adults have been diagnosed with COPD, and similar numbers are thought to have the disease but remain undiagnosed [2]. COPD is responsible for over 140,000 deaths and over $50 billion in combined direct and indirect costs annually in the USA [1,3]. An observational study in the USA found that there were 10.3 million physician office visits, 1.5 million emergency department visits, and 699,000 hospital discharges for COPD in 2010 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, 12 million adults have been diagnosed with COPD, and similar numbers are thought to have the disease but remain undiagnosed [2]. COPD is responsible for over 140,000 deaths and over $50 billion in combined direct and indirect costs annually in the USA [1,3]. An observational study in the USA found that there were 10.3 million physician office visits, 1.5 million emergency department visits, and 699,000 hospital discharges for COPD in 2010 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the age-adjusted prevalence of self-reported HTN among adults in Louisiana was 37.5% in 2015, whereas the national average was 29.8% 8 . Data from the Behavioral Risk Factor Surveillance System between 2014 and 2015 showed that the age-adjusted prevalence of self-reported, physician-diagnosed COPD among adults in Louisiana was about 7.1%; and, 45.3% of those patients listed asthma as a comorbidity 9 . Furthermore, Louisiana has the sixth-highest adult obesity rate in the nation at 36.2% (up from 22.6% in 2000 and 12.3% in 1990); and, while it is not always considered a chronic condition itself, obesity is associated with a high risk for other chronic illnesses like diabetes, HTN, and cardiovascular disease [10][11][12] .…”
Section: Chronic Disease Burdenmentioning
confidence: 99%
“…COPD is a common cause of significant mortality and morbidity in the United States and across the world. [1][2][3] It carries a large financial burden that is mostly attributed to the rate of exacerbations and hospital readmissions. In the United States alone, total medical costs are estimated at $73 billion annually.…”
Section: Introductionmentioning
confidence: 99%